Revelation of modernism responses to cultural crises in fin-de-siècle painting - Boime, Albert 1933-2008 (Univ. of Missouri Press, 2008)
"Examines the work of postimpressionist painters - Van Gogh, Seurat, Cézanne, and Gauguin - and how they responded to cultural and spiritual crisis in the avant-garde world. Boime reconsiders familiar masterpieces and draws analogies with literary sources and social, personal, and political strategies to produce revelations that have eluded most art historians"--Provided by publisher